Effect of therapeutic water of Skhidnitsa region on rehabilitation of patients after nephrectomy for kidney cancer - Pasichnyk, S. M.; Stakhovsky, E. O.; Pasichnyk, M. S.; Gozhenko, A. I.; Myrca, O. Y. (Journal of Education, Health and Sport, 2018)
Among all oncourgical pathologies, in its prevalence, kidney cancer (KC) ranks third after prostate cancer and bladder cancer, and 10th among all malignant neoplasms [1; 3]. KC combines variants of malignant neoplastic transformation of renal tissue in the pathomorphological plan. In adults, kidney-cellular kidney cancer is observed in 80-85% of all primary malignant tumors of the kidney. In Ukraine annually, about 4 thousand new cases of KC are registered [14]. Nearly 60% of new cases are accidentally detected during preventive examinations. [2; 3]. The main method of treatment for KC is to carry out surgical intervention, and the presence of single metastases is often not a contraindication to the operation. Chronic kidney disease (CKD) - occurs due to kidney damage. The most common occurrence of CKD leads to high blood pressure, diabetes mellitus, infectious and inflammatory processes of the kidneys, disorders of urine outflow and tumor lesion of the kidneys. One of the earliest signs of CKD development is the appearance of so-called uric syndrome [14; 15]. Urinary tract syndrome (UTS) in the broad sense, includes all qualitative and quantitative urine changes, and in the narrower - changes in urine sediment: proteinuria, hematuria, leukocyturia. Often, there are some combination of these urinary components (proteinuria with leukocytes, proteinuria with hematuria, etc.). Less commonly, "isolated" proteinuria or hematuria is observed, when other signs are absent or they are expressed insignificantly. As already mentioned, urinary syndrome is considered one of the most important signs of disorders in the urinary system, based on laboratory evidence (statistically significant) and a clear deviation from the norm of urine [5; 16]. In the event that this syndrome is the only manifestation of kidney disease, then an isolated kidney syndrome is diagnosed. Isolated kidney syndrome may occur in primary or secondary glomerulonephritis, as well as in other kidney diseases. However, in order to prevent the development and slow down of the progression of the existing CKD, there is an increased need for adequate rehabilitation therapy in the postoperative period [6; 8; 11; 13]. Consequently, as mentioned above, the issue of the influence of the use of mineral waters of the Skhidnitsky region in the metaphysics of development and progression of chronic renal disease in renal cancer patients undergoing radical nephrectomy remains open today and has not been fully studied [4; 7; 9; 10].